Evaluasi Cement Mill : Neraca Massa dan Neraca Energi pada Cement Mill Indarung V PT Semen Padang - Annisa , Dwi; Parmanaon, Durain; Rahmad, Alfein; Indrianto, Dodi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT Semen Padang, as the largest Cement producer in Indonesia, employs a multi-stage Cement production process, comprising a Raw Mill, a Kiln, and a Cement Mill. The Cement Mill process, serving as the final grinding stage, plays a crucial role in Cement production. Here, clinker, gypsum, pozzolan, and limestone are mixed and ground into Cement, facilitated by grinding media and impact or tumbling forces. This study aimed to investigate the hot gas requirements and efficiency of the a Cement Mill unit, with a focus on the mass balance and energy balance of the Indarung V Cement Mill at PT Semen Padang. The results indicated that the mass of air utilized in the a Cement Mill unit was 132.96 tons/hour, while the water requirement was 3.68 tons/hour. The total mass balance value was 336.95 tons/hour, and the total energy balance value was 4,213,679 Kcal/hour.